Hubungan Kejadian Ibu Hamil yang Terinfeksi Covid-19 terhadap BBLR di UPT Kesmas Blahbatuh II - Agung Aditya Dharmapatni; Komang Triyani Kartinawati; A.A. Sri Agung Aryastuti (Aesculapius Medical Journal, 2023)
The Covid-19 pandemic may concern the birth rate that happens during the pandemic. Low birthweight is a baby that has birth weight of less than 2.500 grams. Indonesia currently stands at the 9th spot with the rate of 15,5% low birthweight out of the total birth each year. This research was held to find the correlation between pregnant mothers afflicted by Covid-19 with the low birthweight in the UPT Kesmas Blahbatuh II area. This research used the analytical quantitative method with the time series method along with the data gathering method of total sampling using medical record and Covid-19 incidents data. The result of this research was 15 total cases of pregnant mothers afflicted by Covid-19 between January 2020 and December 2021, with the peak of these cases was in April 2020. There were a total of 46 cases of low birthweight between January 2020 and December 2021, with the peak of these incidents in October 2021. According to the incident comparison of low birthweight, there is an increase in low birthweight happened within October of 2021 with the number of 6 incidents compared with the same month in 2019. Bivariate analysis shows that there was insignificant correlation between the incident of pregnant mothers afflicted by Covid-19 with the low birthweight incident (p=0,104). Prevention of low birthweight during the pandemic is an early intervention to stimulate a flourishing society.